DATA VISUALIZATION TECHNOLOGIES IN TEACHING ENGLISH AT HIGHER EDUCATIONAL ESTABLISHMENTS - Bogdana Saliuk (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2016)
The article discusses the use of data visualization technologies such as infographics and mind map in teaching foreign languages, particularly English, to students of non-special faculties of the higher educational establishments (programmers, psychologists, engineers, musicians etc). The expediency of introduction of these technologies that will help to relief students' perception of grammatical or lexical material as well as to optimize the educational process and interest in further study of English is noted. Infographics is used for the activation of lexical units, the assimilation of grammatical phenomena, the simulation of real-life situations to develop skills of monologue and dialogue speech, as well as for training in the use of lexical and grammatical material. The practice of English language teaching to students of non-special faculties illustrates the fact that they better perceive English phrasal verbs, thematic vocabulary, grammar, idioms through visualization. At the same time it helps to save time on the explanation of linguistic material in favor of speech activity. Mind map is also useful in the study of lexical and grammatical material in different stages - from the introduction of new themes to its repetition and generalization. Implementing mind map into the educational process the teacher can build the system of communicative exercises, the analysis of professional texts, group, individual and independent work of students.